2019
DOI: 10.1186/s12889-019-7096-3
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol expenditure in grocery stores and their associations with tobacco and food expenditures

Abstract: Background Alcohol consumption is a significant cause of disease, death and social harm, and it clusters with smoking tobacco and an unhealthy diet. Using automatically registered retail data for research purposes is a novel approach, which is not subject to underreporting bias. Based on loyalty card data (LoCard) obtained by a major Finnish retailer holding a market share of 47%, we examined alcohol expenditure and their associations with food and tobacco expenditures. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Participation rate was low and a possible source of selection bias. The participants were unaware of their purchase history use at the time of data collection (Uusitalo et al, 2019). Lacking a 'golden standard', only relative validity could be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Participation rate was low and a possible source of selection bias. The participants were unaware of their purchase history use at the time of data collection (Uusitalo et al, 2019). Lacking a 'golden standard', only relative validity could be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found that shopping baskets with beer as the dominant alcoholic beverage contained more fresh pork, beef, pastries and pickled cucumbers and beetroot than baskets containing cider (Uusitalo et al, 2019).…”
Section: Beer Preferencementioning
confidence: 91%
“…In the ecological studies, the observations had been made on supermarket transactions and shopping events/purchases, rather than on individuals (Berger et al, 2020;Gell and Meier, 2012;Hansel et al, 2015;Johansen et al, 2006;Uusitalo et al, 2019). In the cross-sectional studies, the size of the studied population varied between 423 (Herbeth et al, 2012) and 48,763 (Tjønneland et al, 1999), with an age range of > 18 years old (Ferreira-PĂŞgo et al, 2017) to 85 years old (González-Rubio et al, 2016), and they had been conducted in the following countries between 1997 and 2020: Spain (Alcácera et al, 2008;Carmona-Torre et al, 2008;Ferreira-PĂŞgo et al, 2017;González-Rubio et al, 2016;Sánchez-Villegas et al, 2009;Scholz et al, 2016;Valencia-MartĂ­n et al, 2011), Italy (Chatenoud et al, 2000), France (Hansel et al, 2015;Herbeth et al, 2012;Rouillier et al, 2004;Ruidavets et al, 2004), the Netherlands (Sluik et al, 2014;Sluik et al, 2016b;Sluik et al, 2016c), Denmark (Johansen et al, 2006;Tjønneland et al, 1999), Finland (Männistö et al, 1997;Uusitalo et al, 2019), Belgium (Mullie and Clarys, 2015), the United Kingdom (Berger et al, 2020;Gell and Meier, 2012), and the United States (Barefoot et al, 2002;Forshee and Storey, 2006;McCann et al, 2003;…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is very limited research on using loyalty card data to assess individual and population health. However, a selection of studies shows the potential of loyalty card data for health research [4][5][6][7][8][9][10]. Davies et al [5] used loyalty card data to show a positive correlation between changes in air quality and purchases of cough and cold medication, hay-fever, and pain relief using data of 10 million customers from a major UK supermarket.…”
Section: Introductionmentioning
confidence: 99%